The pronounced effect of Sn on RhSn catalysts for propane dehydrogenation - Natarajan, Prakash; Khan, Hassnain Abbas; Jaleel, Ahsan; Park, Dae Sung; Kang, Dong-Chang; Yoon, Sungho; Jung, Kwang-Deog (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
The pronounced effect of Sn on RhSn/gamma-Al2O3 catalysts for propane dehydrogenation (PDH) is studied. A 0.5wt% Rh/gamma-Al2O3 catalyst (Rh(0.5)) without Sn exhibits very low propane (C-3) conversion (10.7%) and low selectivity (25.4%) for propylene (C-3(=)) at 600 degrees C and a WHSV of 10.8 h(-1). However, the Sn addition to Rh(0.5) increases both the C-3 conversion and the C-3(=) yield. Finally, the Rh(0.5)Sn(3.0) catalyst achieves a C-3 conversion of 30.8% and a C-3(=) selectivity of 96.3%. It has been reported that PtSn catalysts show an optimized C-3(=) at the Sn/Pt molar ratio of about 1.0, increasing the propene selectivity at the expense of catalytic activity. This is not the case for the RhSn system. The primary product of Rh(0.5) is methane (65%) at the initial time and severe coke formation covers the exposed Rh metal, resulting in low C-3 conversion. Both the C-3 conversion and the C-3(=) yield increase with increasing Sn content. The low C-3 conversion and C-3(=) yield of Rh(0.5) are ascribed to cracking via the strong adsorption of intermediates during propane dehydrogenation, resulting in severe coke formation. The main role of Sn on Rh(0.5) in propane dehydrogenation is to suppress cracking of strongly adsorbed intermediates during dehydrogenation; the gain in C-3(=) selectivity outweighs the loss of activity for propane dehydrogenation to propylene up to a high Sn addition of 3 wt%. (C) 2020 Elsevier Inc. All rights reserved.